Cave! Hic Dragones: Understanding Neocolonialism in China’s Economic Diplomacy towards Angola - Salsabila, Ghina; Kusumawardhana, Indra (Global: Jurnal Politik Internasional, 2021)
China is experiencing a fast and dynamic phase of economic development driven by its fast pace of industrialisation. The vast energy demand has pushed China to import energy from other countries with plentiful natural resources. To this aim, China conducts economic diplomacy worldwide, including Angola, a country with plentiful natural resources in Africa. The main concern of this research is China's economic diplomacy which is considered as a form of neocolonialism in this globalisation era. Therefore, the research question of this research is why China's economic diplomacy towards Angola constitutes neocolonialisation. To this aim, this study utilises the Neocolonialism theory in dissecting China's Economic Diplomacy against Angola. This study uses qualitative method with a case study approach using secondary data. Thus, the basis for this research is the author's interpretation. This research concludes that China's economic diplomacy towards Angola constitutes neocolonialisation since the economic means that China exerts on Angola enables China to indirectly control Angola's politics, economy and natural resources, which in turn leads to Angola's dependence on China.